1984
DOI: 10.3109/00016358408993881
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between occlusal factors and signs and symptoms of mandibular dysfunction: A clinical study of 48 dental students

Abstract: Forty-eight young adults answered a questionnaire and were examined clinically for determination of symptoms and signs of mandibular dysfunction in accordance with the Helkimo indices. Occlusal conditions recorded included contacts in centric and excentric mandibular positions in accordance with specified criteria for registration of "ideal occlusion', various occlusal patterns, occlusal interferences, and dental attrition. Relatively frequent but mainly mild signs and symptoms of mandibular dysfunction were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
0
5

Year Published

1985
1985
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 17 publications
5
28
0
5
Order By: Relevance
“…Droukas et al (1984) found a negative correlation between awareness of bruxism and signs of mandibular dysfunction in a group of young students. Recently, Ware & Rugh (1988) suggested that there may be two types of bruxing patients, one bruxing more during rapid eye movement (REM) sleep and one bruxing more during the non-REM phases.…”
Section: Discussionmentioning
confidence: 93%
“…Droukas et al (1984) found a negative correlation between awareness of bruxism and signs of mandibular dysfunction in a group of young students. Recently, Ware & Rugh (1988) suggested that there may be two types of bruxing patients, one bruxing more during rapid eye movement (REM) sleep and one bruxing more during the non-REM phases.…”
Section: Discussionmentioning
confidence: 93%
“…Some epidemiological studies have found associations between occlusal factors and bruxism [3,6,19] and between occlusal factors and symptoms of temporomandibular disorders (TMD) [5], indicating that certain occlusal conditions related to bruxism are potential risk factors for TMD. However, another study does not support these associations because many factors are combined to cause the TMD [4]. Although many theories have been proposed since the 1960s, the etiology of bruxism is still unknown.…”
Section: Introductionmentioning
confidence: 88%
“…[27][28][29] Studies investigating relationships between the occlusion, dental attrition, articular degeneration, alveolar bone changes, and TMD have shown mixed results. [30][31][32][33] Traditionally held beliefs about the role of so-called parafunctional activities (bruxism-clenching and grinding) in the onset of TMD have also not been found to be conclusive. [34][35][36][37][38] Where these activities have been identified as factors in TMD, they have usually been identified as part of a wider (particularly psychoemotional) health concern.…”
mentioning
confidence: 99%